UNDERSTANDING INDIGO THROUGH NOVEL GERBANG DIALOG DANUR BY RISA SARASWATI: A Study of Psychology Literary - Dhinar Ajeng Fitriany; Emzir Emzir; Ninuk Lustyantie (Humanus: Jurnal Ilmiah Ilmu-ilmu Humaniora, 2018)
The objective of this research is to acquire deep understanding about Indigo through novel, Gerbang Dialog Danur’s novel by Risa Saraswati. Danur means of water that comes out from the rotten corpse. This qualitative research was conducted using content analysis method. This research was analyzed through structural literary approach and psychology literary approach. The data were collected through documents, and data observations about Indigo in Gerbang Dialog Danur’s novel by Risa Saraswati. The result of this research revealed that abundance of Indigo and lack of Indigo were founded and described in Gerbang Dialog Danur’s novel by Risa Saraswati. Those results lead to implication that Indonesian literature educator can use Gerbang Dialog Danur’s novel by Risa Saraswati directly in the teaching of literature studies, especially for psychology literary. The findings lead to recommendation to Indonesian literature educator, literature researcher, novel reader, parents, and everyone generally.Keyword: Indigo children, novel, literature, psychology, teaching of literature MEMAHAMI INDIGO MELALUI NOVELGERBANG DIALOG DANUR KARYA RISA SARASWATI: Kajian Psikologi SastraAbstrakTujuan penelitian ini adalah untuk memperoleh pemahaman mendalam tentang Indigo melalui novel, yakni novel Gerbang Dialog Danur karya Risa Saraswati. Danur berarti air yang keluar dari mayat yang busuk. Penelitian kualitatif ini dilakukan dengan menggunakan metode analisis isi. Analisis penelitian dilakukan pendekatan psikologi sastra. Data dikumpulkan melalui studi pustaka, dan observasi data tentang Indigo dalam novel Gerbang Dialog Danur karya Risa Saraswati. Hasil penelitian menunjukkan bahwa kelebihan Indigo dan kekurangan Indigo ditemukan serta digambarkan dalam novel Gerbang Dialog Danur karya Risa Saraswati. Hasil penelitian ini dapat diimplikasikan oleh pengajar sastra Indonesia, yakni dengan menggunakan novel Gerbang Dialog Danur karya Risa Saraswati secara langsung pada proses pengajaran. Hasil penelitian ini direkomendasikan untuk para pengajar sastra Indonesia, pembaca novel, peneliti sastra, para orang tua, dan setiap orang pada umumnya.Kata kunci: anak Indigo, novel, sastra, psikologi, pengajaran sastra